The effect of kinematics and kinetics factors and their partial contribution on the height of standing back somersault - Tang, Ying Wai (2019)
Knowledge of how different biomechanical factors contribute to the vertical displacement of a standing back somersault is important in enhancing the performance. The purpose of this study was therefore to examine the partial contribution of kinematics and kinetics factors on the vertical displacement of a standing back somersault. It was hypothesised that kinematics factors would be a more significant predictor of flight time than vertical ground reaction force. Seven athletes performed eight trials of max effort standing back somersault each. They are proficient in the skill and have at least a year in acrobatic training. Kinematics data were collected from Perception Neuron motion capture system and kinetics data was collected from force platform. The result showed that flight time, which was used as a proxy for vertical displacement, was significantly correlated with vertical ground reaction force (r = -0.42), hip (r = -0.73), shoulder (r = 0.73), knee joint (r = 0.64) and take-off angle (r = 0.38). Ankle joint was found to not have a significant correlation with flight time. The predictor model of flight time was also calculated. It was found that shoulder joint, take-off and knee joint angle were the main predictor of the flight time (r2 = 0.69), in order of entry, with shoulder joint angle alone being able to predict 69% of flight time among participants. It was concluded that kinematics factors were able to predict flight time of standing back somersault more than vertical ground reaction force.